Morphological and genetic variability of the cryptic Gyrodactylus sphinx and Gyrodactylus gerasevi n. sp. (Platyhelminthes: Monogenea) from the Mediterranean Sea and Black Sea: two new members of the cross-ocean distributed Gyrodactylus orecchiae species group. (4th February 2022) - Dmitrieva, E.; Sanna, D.; Vodiasova, E.; Prokhorova, D.; Casu, M.; Burreddu, C.; Piras, M.C.; Garippa, G.; Merella, P.
Abstract: Gyrodactylus sphinx Dmitrieva & Gerasev, 2000 is the only species of Gyrodactylus originally described from Aidablennius sphynx (Valenciennes) in the Black Sea. In the present study, monogeneans similar to G . sphinx are reported from the same host and from two other species of Blenniidae from the Black Sea, as well as from the Mediterranean Sea. This study aims to verify the taxonomic status of the specimens found in different hosts and localities, other than the type ones of G . sphinx . Twenty-two measurements of the haptoral structures of 169 gyrodactylids were used for the morphological study. Morphometric variability between different samples was analysed using analysis of variance, multivariate analysis of variance (MANOVA) and principal component analysis (PCA). Molecular studies were carried out using the nuclear internal transcribed spacer 2 and 5.8S ribosomal DNA regions. Network, Bayesian phylogenetic and species delimitation analyses were performed to infer the number of taxonomic units and the phylogeographic relationships occurring within and among them. MANOVA revealed a significant dependence of the morphometry of hamuli and marginal hooks on host species and regions, but a clear differentiation between samples was not confirmed by PCA. Moreover, the ranges of all dimensions overlapped between samples. However, molecular analyses suggested the occurrence of at least two taxonomic entities. The most common entity was present in individuals of the Black and Mediterranean seas, and is described here as Gyrodactylus gerasevi n. sp., whereas a second entity recognized as a G . sphinx was found only in individuals from two localities off Crimea. The monophyletic cluster grouping of these two species was placed within a large clade that also included a separate sister cluster with seven other species of the Gyrodactylus orecchiae cross-ocean species group.